PEMANFAATAN TEMPE DAN UBI JALAR MERAH DALAM PEMBUATAN MIE BASAH SERTA UJI DAYA TERIMANYA (The Utilization of Tempe and Red Sweet Potatoes in Manufacture of Wet Noodles and Organoleptic Test) - Sri Erlina; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Noodle is one of the most popular types of food in the community. Currently, the noodle was made as a replacement food of other staple foods such as rice. Generally, raw material of noodle is flour. However, the flour can also be modified with other foods such as tempe and red sweet potato. The purpose of  this research is to know the comparative influence of wheat flour, tempe and red sweet potato. This research is an experimental study which is designed by a random draft  with two factors namely red sweet potato and tempe by comparison (30% : 20%, 25% : 25%, 20% : 30%). The influence of addition  tempe and  red sweet potato were analyzed with anova test and double Duncan test. The parameters analyzed  include the lucrative nature of the organoleptic color, aroma, taste and texture of wet noodle. The results showed that the organoleptic test colors, aromas, and flavors of the most preferred wet noodle is noodles tempe with the addition of 20%, and red sweet potato 30% while the wet noodle texture is the most preferred panelist is wet noodle tempe with the addition of 25% and 25% red sweet potato. Based on the analysis of anova (α=5%), The addition of tempe and red sweet potato with different concentration on the creation of a wet noodle gave different effects to the color, aroma and flavor. But didn’t give a different affect on the texture of a wet noodle. Keywords : wet noodle, tempe, red sweet potato, organoleptic test